2021
DOI: 10.1002/jimd.12467
|View full text |Cite
|
Sign up to set email alerts
|

Oral treatment for mucopolysaccharidosis VI: Outcomes of the first phase IIa study with odiparcil

Abstract: Mucopolysaccharidosis (MPS) disorders are a group of rare, progressive lysosomal storage diseases characterized by the accumulation of glycosaminoglycans (GAGs) and classified according to the deficient enzyme. Enzyme replacement therapy (ERT) of MPS VI has limited effects on ophthalmic, cardiovascular, and skeletal systems. Odiparcil is an orally available small molecule that results in the synthesis of odiparcil‐linked GAGs facilitating their excretion and reducing cellular and tissue GAG accumulation. Impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In these studies, availability of odiparcil was demonstrated in vitro and in vivo assays including administration test using ARSB knock-out mice. The availability of odiparcil as therapeutic drug for MPS VI is examined in phase II trials [ 24 ]. The generated MPS VI human mutation knock-in mice are useful models for trials of novel therapeutic approaches.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, availability of odiparcil was demonstrated in vitro and in vivo assays including administration test using ARSB knock-out mice. The availability of odiparcil as therapeutic drug for MPS VI is examined in phase II trials [ 24 ]. The generated MPS VI human mutation knock-in mice are useful models for trials of novel therapeutic approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have confirmed beneficial effects of odiparcil in animal models of MPS VI [ 15 , 17 , 23 ]. Evidence for improvement in COM was observed in a Phase 2a study of odiparcil in patients with MPS VI [ 24 ]. To apply the new therapy in the clinical setting, a quantitative measurement is necessary to evaluate and monitor the severity of corneal clouding in MPS VI patients.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was in good agreement with previous studies demonstrating higher CIMT in various types of MPS patients compared with controls [ 19 , 30 , 32 ]. In the Phase 2 study, improvement in CIMT was observed in patients treated with odiparcil [ 24 ]. CIMT is correlated with carotid pathology and has been used as a marker predictive of cerebrovascular accidents in other chronic conditions including diabetes mellitus and hypertension [ [32] , [32] , [33] , [34] ].…”
Section: Discussionmentioning
confidence: 99%
“…Although not approved, this reagent was originally developed as an anticoagulant [390,391]. Subsequently, its role in reducing accumulated GAGs was reconsidered, and a phase 2 clinical trial for MPS VI patients was completed [392]. Participants in this study were between 16 and 64 years of age, so, as Guffon et al pointed out, further evaluation of odiparcil in younger patients should be considered.…”
Section: Other Potential Therapies In the Futurementioning
confidence: 99%